Results Of Rational Psychotherapy In Plastic Surgery Practice Of Changing The Appearance - Polvanov Rasulbek Baxtiyarovich; Ibodullaev Zarifboy Radjabovich; Boymurodov Shuxrat Abdujalilovich; Nigmatov Iftixor Obidjon O'g'li (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
Rasional psychoterapiya (rpt) is distinguished from other psychoterapetic techniques by its simplicity, no special psychological exercises are required, easy reception by patients and the result is quickly noticeable [1-3]. During psychotic Sessions, psychotic experiments are not conducted, the patient is not encouraged to perform various tasks, giving the House special tasks, the next day his answer is not asked. This means that in rpt the patient is put freely and the existing psychological conflicts in it are easily resolved [6-7].